PERAN KEGIATAN EKSTRAKURIKULER PRAMUKA DALAM MEMBENTUK KARAKTER DISIPLIN PESERTA DIDIK SEKOLAH DASAR KELAS TINGGI - Ayu Alit Diah Pitaloka, Ida; Hariyanto; Wicaksono, Lungit; Destini, Frida (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study analyzes the role of extracurricular scouting activities in forming the character of discipline in high-grade elementary schools. Strengthening the formation of disciplined character is important considering the many moral crisis incidents in various groups, including children. Therefore, character formation needs to be honed as early as possible. This study uses a qualitative method with data collection techniques in the form of observation, interviews, and documentation. The results of the study show that extracurricular scouting activities play a role in forming a disciplined character by getting students used to arriving on time, obeying existing rules, completing assignments on time and using good and correct language. (1) forms of scouting activities designed to form a disciplined character through physical training (PBB, pioneering, ropes and others), ceremonies (morning roll call), and social interactions (group activities and forming a squad). (2) Through the process of instilling habits with various forms of activity, over time students will start to get used to doing things such as arriving on time, obeying existing rules, doing assignments on time and using good and correct language repeatedly, so that students can have good personalities and discipline during scouting activities and in their daily routines in the school environment.